Peningkatan Kualitas Kinerja Tata Kelola Arsip Desa Melalui Program KKM: Studi kasus di Desa Sukamulya Kecamatan Mekarjaya Kabupaten Pandeglang - Rakhmat Bakhtiar (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
This study aims to find out how archive management supports administrative services at the Sukamulya village office, Pandeglang Regency. This research uses descriptive method with qualitative data. Observations included the implementation of the village archive management process and efforts to improve the capacity of village apparatus in archival management. The data analyzed were the results of observations and interviews with the village head and village secretary. The results of the study show that the governance of the Sukamulya village office archives refers to classification patterns, guidelines for managing letters, and guidelines for organizing files, but the implementation is still not optimal. This is related to the lack of existing human resources and the absence of a filing plan including budgeting. The efforts made to increase the ability of village apparatus in archival management are by holding archival seminars and training which are directly led by the Library and Archives Service of the Pandeglang Regency as an advisory agency for archivists at the District and Village levels.